2015
DOI: 10.1073/pnas.1406495111
|View full text |Cite
|
Sign up to set email alerts
|

Public health impacts of ecosystem change in the Brazilian Amazon

Abstract: The claim that nature delivers health benefits rests on a thin empirical evidence base. Even less evidence exists on how specific conservation policies affect multiple health outcomes. We address these gaps in knowledge by combining municipal-level panel data on diseases, public health services, climatic factors, demographics, conservation policies, and other drivers of land-use change in the Brazilian Amazon. To fully exploit this dataset, we estimate random-effects and quantile regression models of disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 54 publications
4
87
0
5
Order By: Relevance
“…The ambiguity in the latter cases arose from varying results based on mosquito species in question and the landscape context [42], the type of forest studied (sustainable forest reserve versus protected forest reserve; [45]), or the metric used to measure malaria (entomological inoculation rate (EIR) versus human-biting rate (HBR); [46]). Also, five of these 12 papers supported the idea that initial deforestation in new settlements increases malaria risk, but as deforestation proceeds it can translate into lower malaria risk [13,17,3739].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambiguity in the latter cases arose from varying results based on mosquito species in question and the landscape context [42], the type of forest studied (sustainable forest reserve versus protected forest reserve; [45]), or the metric used to measure malaria (entomological inoculation rate (EIR) versus human-biting rate (HBR); [46]). Also, five of these 12 papers supported the idea that initial deforestation in new settlements increases malaria risk, but as deforestation proceeds it can translate into lower malaria risk [13,17,3739].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…land clearing, logging, extraction of forest products, hunting and fishing) increase human contact with malaria vectors leading to a rise in malaria cases, but only 57% of these (4 of 7) collected survey data to test this relationship [16,19,56,57]. The association between forest-related activities and malaria is supported by Bauch et al [45], who found that strictly protected forest areas promote lower malaria transmission, while sustainable-use protected areas are associated with higher malaria transmission. On the other hand, Barros et al [58] and Silva-Nunes et al [19] found no evidence that activities like hunting or fishing, which involve sleeping away from home (outside), increase malaria risk.…”
Section: The Environmentmentioning
confidence: 99%
“…Although recent work has begun to describe the varied ways in which natural systems affect human health and well-being [66,67; see also Bauch et al (68) in this issue], the paucity of models and tools for exploring A framework for including natural capital in the broader context of formal and informal decision-making institutions along with other forms of capital: financial, human, manufactured, and social. Formal and informal institutions influence decisions by both service providers and beneficiaries.…”
mentioning
confidence: 99%
“…The appeal of the dilution effect has been recognized by others: “the desire to make the case for conservation has led to broad claims regarding the benefits of nature conservation for human health” (Bauch et al. ). Randolph and Dobson () were among the first to critique these claims, making the case that promotion of conservation to reduce Lyme disease risk, although well intentioned, was flawed.…”
mentioning
confidence: 99%
“…Malaria transmission in the Brazilian Amazon is high in protected areas that allow people access to forest, but low around protected areas where people are prevented from entering (Bauch et al. ). Ignoring this study and the many others like it makes it impossible for Levi et al.…”
mentioning
confidence: 99%